(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
The research problem stems from the absence of a defined methodology for applying Resource Consumption Accounting (RCA) in a manner that effectively contributes to cost reduction in product manufacturing. This gap necessitated the development of a scale to measure product quality as a means to achieve competitive advantage. The study sought to address the following key questions: To what extent does the implementation of the RCA method enhance product quality and support competitive advantage? What impact does the use of RCA have on reducing financial costs and optimizing resource utilization to attain competitive advantage? The primary objectives of the research were to evaluate the effectiveness of RCA in improving product quality and to explore its role in minimizing financial costs while maximizing resource efficiency - all in pursuit of competitive advantage. The study was guided by a central hypothesis: There exists a statistically significant relationship between the application of RCA in enhancing product quality and in reducing financial costs, both contributing to the attainment of a competitive advantage. The researcher adopted a multi-method approach, including the deductive method for hypothesis formulation, the inductive method for hypothesis testing, as well as analytical statistical, historical, and descriptive methodologies. The findings revealed that implementing the RCA system enables the production of high-quality products and enhances the firm’s competitive position. The RCA system positively influenced customer perceptions regarding the company’s competitive advantage. Moreover, it played a crucial role in identifying direct production costs, thereby contributing to improved product quality and competitive positioning. The study recommends leveraging administrative and marketing costs to deliver greater value to customers compared to competitors. It further advocates for the application of RCA strategic axes—such as differentiation, focus strategies, and comprehensive cost leadership—as integral tools for achieving and sustaining competitive advantage. Additionally, it emphasizes the need to increase reliance on the RCA system to support the effective use of cost management tools in reinforcing competitive positioning.